(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study compared how two learning management systems (LMS), the Blackboard system and bright space, are perceived by Bestlink College of the Philippines Grade 12 General academic strand students; according to the report, using an LMS has advantages, including making it simple to access shared data and files monitoring and recording student performance personalizing the learning experience and promotion dialogue. In terms of Module Content, the first variable shows a weighted mean of (2.76), and the verbal interpretation is (Agree). The second variable is accessibility. The weighted mean is (2.84), and the verbal interpretation is (Agree). It came up by the following students and respondents of this questionnaire. According to the survey, students who use the Brightspace system are more aware of the benefits of e-learning than students who use the Blackboard system. According to the study, by selecting the proper strategies to promote sustainable teaching and learning, these findings can assist educators in adopting open and distance learning efficiently. As an evaluation strategy, the study uses developmental evaluation (DE), which provides a deeper degree of analysis to comprehend the role.